SemWeB: A Semantic Web Browser for Supporting the Browsing of Users Using Semantic and Adaptive Links. - Sah, M; Hall, W; Roure, D (Springer, 2008)
Web browsing is a complex activity and in general, users are not guided during browsing. The aim of this research is to support the browsing of users using semantic and adaptive hyperlinks using Semantic Web technologies and personalization methods. In this paper, we propose a novel Semantic Web browser (SemWeB), which uses a behavior-based and an ontology-driven user modeling architecture. In our approach, semantic links and adaptive hypermedia can be achieved on different websites. In addition, user profiles can be easily updated with semantic metadata coming from the Semantic Web browser. © Springer-Verlag Berlin Heidelberg 2008.